CURRENT STATE OF DIGITALIZATION IN THE SPHERE OF PHYSICAL CULTURE AND SPORTS IN UKRAINE (Physical Culture and Sport: Scientific Perspective, 2023)
It has been established that the development of digitalization in Ukraine in the field of physical culture and sports plays one of the most important roles in the life of a person and society. The level of the average life expectancy of citizens, the level of health and the general moral and psychological state of the population depends on the physical literacy of the country. Therefore, the level and development of an effective mechanism for the formation of physical culture and sports in people of all ages is one of the priority directions of the state's internal policy with the aim of forming a healthy and competitive nation. It is clear that in Ukraine there are a number of normative documents that regulate the development of physical culture and sports in the direction of digitalization: "Strategy for the implementation of digital development, digital transformations and digitalization of the state financial management system for the period until 2025 and approval of the plan of measures for its implementation" , "Strategy for the development of physical culture and sports for the period until 2028". It is emphasized that today the Ministry of Youth and Sports of Ukraine has a separate digital direction. The result of which is the active implementation of sports startups. It is summarized that, according to the Ministry of Youth and Sports of Ukraine, in 2022, 12 projects of Ukrainian sports startups took part in obtaining subscriptions for membership in The Global Sports Innovation Center powered by Microsoft (GSIC), where the winners were "12Climb",“AiSport”, “Streetball App”. It was determined that there is a sufficient level of involvement of citizens in the field of physical culture and sports in Ukraine, and that in order to strengthen the general health of citizens, sustainable moral and psychological development and general physical education, it is necessary to further improve measures of state support for the development of this direction. Digital transformation in the field of physical culture and sports is one of these measures.
Keywords: digitalization; physical culture; digital technologies; sports startups; digital development